Requisite expertise, firm reputation, and status in venture capital investment allocation decisions - Dimov, Dimo; Shepherd, Dean A.; Sutcliffe, Kathleen M. (Journal of Business Venturing, 2007)
Drawing together research in the upper echelon perspective, strategy, and organizational sociology, this paper examines (1) the relationship between the finance expertise of a venture capital (VC) firm's management team and investment selection, and (2) the moderation of this relationship by the VC firm's social position. We find that while finance expertise is associated with a lower proportion of early-stage investments, this relationship is weaker for firms with high reputation and stronger for firms with high status. We conclude with a discussion of the importance and nuances of external image considerations on investment decisions as well as insights into the importance of the requisite nature of expertise.